Neurophysiological Characteristics of Cranial Nerves V- and VII-Triggered EMG in Endoscopic Endonasal Approach Skull Base Surgery - Ferreira, Carla J.A.; Sherer, Marcus; Anetakis, Katherine; Crammond, Donald J.; Balzer, Jeffrey R.; Thirumala, Parthasarathy D. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective This study proposes to present reference parameters for trigeminal (V) and facial (VII) cranial nerves (CNs)-triggered electromyography (tEMG) during endoscopic endonasal approach (EEA) skull base surgeries to allow more precise and accurate mapping of these CNs.Study Design We retrospectively reviewed EEA procedures performed at the University of Pittsburgh Medical Center between 2009 and 2015. tEMG recorded in response to stimulation of CN V and VII was analyzed. Analysis of tEMG waveforms included latencies and amplitudes. Medical records were reviewed to determine the presence of perioperative neurologic deficits.Results A total of 28 patients were included. tEMG from 34 CNs (22 V and 12 VII) were analyzed. For CN V, the average onset latency was 2.9 ± 1.1 ms and peak-to-peak amplitude was 525 ± 436.94 μV (n = 22). For CN VII, the average onset latency and peak-to-peak amplitude were 5.1 ± 1.43 ms and 315 ± 352.58 μV for the orbicularis oculi distribution (n = 09), 5.9 ± 0.67 ms and 517 ± 489.07 μV on orbicularis oris (n = 08), and 5.3 ± 0.98 ms 303.1 ± 215.3 μV on mentalis (n = 07), respectively.Conclusion Our data support the notion that onset latency may be a feasible parameter in the differentiation between the CN V and VII during the crosstalk phenomenon in EEA surgeries but the particularities of this type of procedure should be taken into consideration. A prospective analysis with a larger data set is necessary.
Keywords: endoscopic endonasal approach; intraoperative neuromonitoring; triggered electromyography; trigeminal and facial nerves; crosstalk phenomenon